Towards eco-efficiency of OECD countries: How does environmental governance restrain the destructive ecological effect of the excess use of natural resources? - Brahim Bergougui; Elma Satrovic (Ecological Informatics)
Developed economies face mounting environmental challenges from excessive resource consumption, but we lack clear evidence on how environmental policies can best address these issues. This study investigates how environmental governance shapes resource use and ecological efficiency across nine OECD countries from 1997 to 2020. Our analysis reveals that stronger environmental policies significantly improve eco-efficiency: a 1 % increase in environmental governance effectiveness enhances eco-efficiency by 0.65–0.95 %, with the strongest effects observed in countries currently showing lower ecological efficiency. We find that increasing energy transition efforts and research and development investment each contribute to improved eco-efficiency (0.07–0.11 % and 0.19–0.35 % respectively), while excessive resource use reduces it by 0.07–0.03 %. Notably, our study introduces a novel analytical approach by examining how environmental policies moderate the negative impacts of resource overuse across different levels of ecological efficiency. This relationship proves especially important for countries struggling with lower eco-efficiency, where strong environmental governance can effectively offset the harmful effects of excessive resource consumption. These findings remain consistent across multiple measures of eco-efficiency and trade indicators, offering robust evidence for policymakers. Our research provides practical guidance for balancing economic development with environmental protection through targeted policy interventions, particularly in resource-intensive economies working to improve their ecological performance.